2017
DOI: 10.1155/2017/7361896
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Traditional Chinese Medicine Body Constitution Associated with Overweight, Obesity, and Underweight

Abstract: Objective The aim of the study was to investigate the associations among the nine types of body constitution in traditional Chinese medicine (TCM) with the outcomes of overweight, obesity, and underweight. Method Participants aged 30 to 90 years were recruited from communities in Shanghai and assessed using a self-administered questionnaire pertaining to their demographics, lifestyles, and self-reported medical history. The data of 3748 participants with complete information was available for the analysis. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…In TCM theory, people are divided into nine types of body constitution, among which ASDs are associated with Qi _Stagnation, which can lead to “ Yu ” syndrome [ 33 ]. As a result of long-term emotional disorder, Qi _stagnation forms through personality instability, melancholy, sensitivity, and suspiciousness as the main body state.…”
Section: Discussionmentioning
confidence: 99%
“…In TCM theory, people are divided into nine types of body constitution, among which ASDs are associated with Qi _Stagnation, which can lead to “ Yu ” syndrome [ 33 ]. As a result of long-term emotional disorder, Qi _stagnation forms through personality instability, melancholy, sensitivity, and suspiciousness as the main body state.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the principles of TCM were derived from the traditional Chinese philosophical basis (eg, Taoism and Confucianism), and Yin and Yang were the fundamental conception of TCM 21. For TCM, the systematic body constitutional theory was recently proposed 23. A number of previous studies demonstrated that body constitution was associated with obesity, diabetes and a cluster of metabolic indicators 22–24.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…For TCM, the body constitution refers to an individual character compatible with nature and the social environment and might indicate the susceptibility to diseases, metabolism and response to stimuli 23. Several cross-sectional studies have revealed that body constitution is associated with certain NCDs, such as obesity and diabetes 22–24.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Constitution identification, also known as the "four diagnostics of TCM," which traditionally involve looking, hearing, and consultation, is a crucial process in the practice of TCM [2]. Constitution identification can be applied not only to patients [3][4][5] but also to the general population to help people better understand their health status to prevent disease [6]. This paper will focus on the relationship between tongue diagnosis, consultation and constitution.…”
Section: Introductionmentioning
confidence: 99%